Computational optimization of the internal cooling passages of a guide vane by a gradient-based algorithm. (17th June 2016) - Xie, Gongnan; Song, Yidan; Sundén, Bengt
ABSTRACT: To keep the spatially averaged temperature and thermal stress of gas turbine blades and guide vanes within a permissible level, the present research concentrates on the optimization of the internal cooling passages in a guide vane. The main purpose is to search for the most optimal sizes, distributions, and shapes of internal cooling channels located in a guide vane. Cylindrical cooling passages and newly built passages shaped by Bezier curves are both considered in this investigation. In order to maintain the shapes of the cooling channels within the scale of the vane profile, a new technique is suggested to discretize the vane into the components, and then the outline of the passages is built based on the components. The optimization of sizes, locations, and shapes of the cooling passages is solved as a single-objective problem using a gradient-based optimization algorithm, i.e., the globally convergent method of moving asymptotes (GCMMA). The optimized result displays a substantial reduction in both the spatially averaged temperature and thermal stress of the vane, and the related configurations are included and discussed in the investigation.